Social conflict analysis on a mining project using shannon entropy - Delgado, Alexi (2017)
Social conflicts in the world have increased, due to the fact that the natural resources is being over exploited. In this work, we conducted a social conflict analysis using the entropy-weight method, which is based on Shannon entropy theory. The case study was conducted on a mining project allocated in northern Peru. The rural population and urban population stakeholder groups were analyzed under seven social criteria or variables. The results revealed that the criterion most likely to generate social conflict between stakeholder groups was access to drinking water. These results could help to central and local governments to make the best decision in order to prevent possible social conflict. The entropy-weight method showed interesting results and could be applied to other social conflicts, as this method considers the uncertainty within its analysis.